Electromagnetic interaction with uniaxial metamaterials. Issue 7 (8th July 2015) - Tedeschi, N.; Frezza, F.; Sihvola, A.
Abstract In this paper, the reflection behavior of a particular class of metamaterials, strongly connected with the realization of the DB boundary conditions (so called due to the vanishing of the normal components of the D and B fluxes) and the soft and hard (SH) boundary conditions, is presented. The metamaterial under study is modeled as an anisotropic, uniaxial, material with both permittivity and permeability dyadics. We consider several characteristics of such medium: presenting the critical angle of total transmission for the SH/DB material, analyzing its behavior as a function of the longitudinal permittivity and permeability, for both positive and negative values, and presenting its applications to the electromagnetic absorbers and to the polarization inverters.